Aktivitas Antioksidan Ekstrak Etanol, Etil Asetat, Dan n-Heksan Biji Mengkudu (Morinda Citrifolia L.) Dengan Metode DPPH - Nurisyah, Nurisyah; Irawati, Irawati; Salasa, Alfrida Monica; Asyikin, Asyhari (Media Farmasi, 2024)
Antioxidants are compounds that can reduce the negative impact of free radicals. Noni seeds (Morinda citrifolia L.) contain these compounds as secondary metabolites. This research is a laboratory observational study to determine and compare the antioxidant activity of ethanol extract, ethyl acetate extract, and n-hexane extract noni seeds (Morinda citrifolia L.) using the 1,1-diphenyl-2- picrylhydrazyl method using a UV-Vis Spectrophotometer at a wavelength of 516 nm. The results showed that the IC50 value of the ethanol extract of noni fruit seeds was 507.75 ppm and the IC50 value of the ethyl acetate extract of noni fruit seeds was 43.18 ppm, while the n-hexane extract of noni fruit seeds had inactive antioxidant activity. The antioxidant activity of the ethanol extract of noni seeds is in the weak category and the antioxidant activity of the ethyl acetate extract is in the very strong category. The extracting solution that produces noni seed extract with the highest antioxidant activity is ethyl acetate solvent